A hyper-acute immune hemolytic anemia induced by contrast medium was successfully treated with eculizumab: a case report - Hermann, Sabine; Althaus, Karina; Mustafi, Migdat; Mayer, Beate; Rosenberger, Peter; Haeberle, Helene Anna; Bernard, Alice (Frontiers in Immunology, 2025)
Contrast medium is frequently associated with allergic reactions and kidney dysfunction. However, contrast media can induce hemolytic anemia with a broad spectrum of hemolytic manifestations. We report a 38-year-old patient with very severe immune hemolytic anemia after the application of iomeprol due to a CT of the thorax/abdomen. In this case report, we illustrate the diagnostics and treatment of life-threatening hemolytic anemia induced by a contrast medium that was successfully treated with eculizumab.